Determination of enzymes of glycolysis and oxidative phosphorylation in lymphocytes in patients with immuno-dependent diseases - T. V. Radygina; S. V. Petrichuk; O. V. Kurbatova; D. G. Kuptsova; A. S. Potapov (Аллергология и Иммунология в Педиатрии)
.